Electronic Alert System Significantly Increases HBV Screening Rates Before Immunosuppressive Treatments - Köksal, Aydın Şeref; Toka, Bilal; Sadeçolak, Mustafa; Acar, Şencan; Eminler, Ahmet Tarık; Tozlu, Mukaddes; Karabay, Oğuz (Turkish Journal of Gastroenterology, 2023)
Background: Hepatitis B Virus (HBV) screening rates before starting immunosuppressive treatments are suboptimal. The aim of the study was to evaluate the efficacy of a new electronic alert system in increasing HBV screening rates. Methods: The electronic alert system, HBVision2, identifies patients at risk of HBV reactivation when a pre-determined International Classification of Diseases (ICD)-10 code is entered into the hospital’s database or immunosuppressive treatment is prescribed. The system evaluates the prior Hepatitis B Surfage Antigen (HBsAg) and anti-Hepatitis B Core Immunglobulin G (HBc IgG) results and sends an alert code to the clinician for screening if serology is not completely available or consult a specialist in case of positive serology. The HBV screening and consultation rates of patients before (control group) and after HBVision2 were retrospectively compared. The clinical course of unscreened and/or unconsulted patients was determined, and the clinical efficacy of HBVision2 in preventing HBVr was predicted. Results: Control group included 815 patients (52.6% male, mean age: 60 ± 12, 82.5% with oncologic malignancy) and study group included 504 patients (56% male, mean age: 60 ± 13, 91.4% with oncologic malignancy). Groups were similar with respect to gender, mean age, and HBVr risk profile of the immunosuppressive treatment protocols. Overall, both HBsAg (from 55.1% to 93.1%) and anti- HBc IgG screening rates significantly increased (from 4.3% to 79.4%) after the electronic alert system (P < .001, for both). Consultation rates of anti-HBc IgG-positive patients significantly increased from 40% to 72.7% (P = .012). HBVr developed in 2 patients (2.6%) who were not screened and/or consulted after the alert system. Alert program prevented the development of HBVr in 10 patients (1.9%) of the study group and decreased the development of HBVr by 80%. Conclusion: Electronic alert system significantly improved HBsAg and anti-HBc IgG screening rates before starting immunosuppressive treatment and prevented the development of HBVr to a great extent. However, screening rates are still below optimal and need to be improved.